The Tangled Roots of Family, Forest, and Farm - Jagoe, Eva-Lynn (Journal of Ecohumanism, 2023)
When my family started stewarding eight acres in British Columbia, Canada, we encountered a pervasive pioneer species or â€œweedâ€â€”quackgrassâ€”that grows long roots and chokes out other plants. This paper counterposes the behaviour of these competitive and embinding roots with the cooperative mutual interrelation of forest root systems. Using these two roots as metaphors for the pleasures and pitfalls of family, I will make an argument for family farming that both honours and resists the tangle of rootedness that is embodied in the symbiotic relationship of mother and sons. I paint a picture of a political project of regeneration and flourishing that is founded on deep love and affinity for the land and for each other. While I critique the constraints of family, the mother-son relationship emerges in this essay as a historically embedded and potentially generative form of community.